A strategy for the finite element modeling of FRP-confined concrete columns subjected to preload. (15th October 2018) - Ferrotto, M.F.; Fischer, O.; Cavaleri, L.
Highlights: Behavior of concrete columns subjected to preload before FRP-wrapping is presented. The study is carried out by means of Finite element modeling Abaqus software. Experimental-numerical results indicate the preload affects the compressive response. Abstract: Compressive behavior of columns strengthened by means of an outer elastic confinement provided e.g. by fiber-reinforced polymer (FRP) jackets has become a main topic in the field of structural retrofitting. In details, the problem of the response assessment of strengthened columns is still under study. Many analytical formulations have been proposed to describe the compressive behavior of confined concrete under both monotonic and cyclic loads. However, the effect of a stress/strain level in the columns already present prior to apply the confinement has been generally neglected until now, also because of the lack of well defined strategies of modeling. In this frame, here, (1) a FEM assessment strategy is presented and discussed referred to FRP-confined reinforced concrete columns subjected to monotonic compressive loads; (2) to this aim, first, a modified stress-strain law for the concrete is proposed for the FE analysis able to capture the softening/hardening behaviour differently from the laws of unconfined concrete commonly used as input; (3) then a law to fix the parameters defining the hardening/softening characteristics starting from the characteristics of the unconfined concrete and of the FRP wrapping is provided. After calibrating and validating the above strategy in the case of non preloaded elements, the compressive behavior in the presence of preload is analyzed numerically and compared with experimental results to evaluate the reliability of the FE model approach proposed. Through the paper, the procedure for the definition of the law to fix the hardening/softening parameters of the concrete is described.